The short-term effect of whole-body vibration training on vertical jump, sprint, and agility performance - Cochrane, D. J.; Legg, S. J.; Hooker, M. J. (The Journal of Strength and Conditioning Research, 2004)
Previous studies have suggested that short-term whole-body vibration (WBV) training produces neuromuscular improvement similar to that of power and strength training. However, it is yet to be determined whether short-term WBV exposure produces neurogenic enhancement for power, speed, and agility. The purpose of this study was to investigate the effect short-term WBV training had on vertical jump, sprint, and agility performance in nonelite athletes. Twenty-four sport science students (16 men and 8 women) were randomly assigned to 2 groups: WBV training or control. Each group included 8 men and 4 women. Countermovement jump (CMJ) height, squat jump (SJ) height, sprint speed over 5, 10, and 20 m, and agility (505, up and back) were performed by each participant before and after 9 days of either no training (control) or WBV training. Perceived discomfort of every participant was recorded after daily WBV exposure and nonexposure. There were no significant differences between WBV and control groups for CMJ, SJ, sprints, and agility. Perceived discomfort differed between the first and subsequent days of WBV training (p < 0.05); however, there was no difference between the WBV and control groups. It is concluded that short-term WBV training did not enhance performance in nonelite athletes.